Yard vegetation is associated with gut microbiota composition - Parajuli, Anirudra; Hui, Nan; Puhakka, Riikka; Oikarinen, Sami; Grönroos, Mira; Selonen, Ville A O; Siter, Nathan; Kramna, Lenka; Roslund, Marja I; Vari, Heli K; Nurminen, Noora; Honkanen, Hanna; et al. (The Science of the total environment, 2020)
Gut microbes play an essential role in the development and functioning of the human immune system. A disturbed gut microbiota composition is often associated with a number of health disorders including immune-mediated diseases. Differences in host characteristics such as ethnicity, living habit and diet have been used to explain differences in the gut microbiota composition in inter-continental comparison studies. As our previous studies imply that daily skin contact with organic gardening materials modify gut microflora, here we investigated the association between living environment and gut microbiota in a homogenous western population along an urban-rural gradient. We obtained stool samples from 48 native elderly Finns in province Häme in August and November 2015 and identified the bacterial phylotypes using 16S rRNA Illumina MiSeq sequencing. We assumed that yard vegetation and land cover classes surrounding homes explain the stool bacterial community in generalized linear mixed models. Diverse yard vegetation was associated with a reduced abundance of Clostridium sensu stricto and an increased abundance of Faecalibacterium and Prevotellaceae. The abundance of Bacteroides was positively and strongly associated with the built environment. Exclusion of animal owners did not alter the main associations. These results suggest that diverse vegetation around homes is associated with health-related changes in gut microbiota composition. Manipulation of the garden diversity, possibly jointly with urban planning, is a promising candidate for future intervention studies that aim to maintain gut homeostasis.
Keywords: Gastrointestinal Microbiome; Feces; střevní mikroflóra; Bacteria; RNA ribozomální 16S; feces; Animals; Humans; Built area coverage; Garden diversity; lidé; Gut microbiota; Living environment; zvířata; Elderly gut microbiota; Bacteroides; RNA, Ribosomal, 16S